2021
DOI: 10.1186/s43019-021-00088-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: total knee arthroplasty (TKA) in patients with pigmented villonodular synovitis (PVNS)

Abstract: Background To determine the functional outcomes, complications and revision rates following total knee arthroplasty (TKA) in patients with pigmented villonodular synovitis (PVNS). Materials and methods We conducted a systematic review of the literature. Five studies with a total of 552 TKAs were included for analysis. The methodological quality of the articles was evaluated using the Strengthening the Reporting of Observational Studies in Epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…For example, some authors have reported the STROBE reporting checklist as a scale. 11 The findings reported here suggest that there may be important weaknesses in the background of the authors regarding their knowledge of the methodological aspects of research. It appears that some may have just adopted an approach in their systematic reviews based on what has already been done in the past without questioning its validity.…”
mentioning
confidence: 77%
“…For example, some authors have reported the STROBE reporting checklist as a scale. 11 The findings reported here suggest that there may be important weaknesses in the background of the authors regarding their knowledge of the methodological aspects of research. It appears that some may have just adopted an approach in their systematic reviews based on what has already been done in the past without questioning its validity.…”
mentioning
confidence: 77%
“…The combined anterior arthroscopic and posterior open synovectomy in the knee could be a good option because some researches have shown that the recurrence rate of it is lower than arthroscopic synovectomy and open synovectomy. In addition, if there is a destructive change in the joint surface that cannot be treated by synovectomy alone, total knee arthroplasty can provide a reliable improvement in function, but the risk of knee stiffness is significantly increased after total knee arthroplasty which should be noted [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%
“…14 It has been shown that this patient population has a higher rate of complication after undergoing TKA, and PVNS recurrence was seen in 12% of patients at the 10-year post-operative time point, all requiring re-operation. 23 24 Casp et al performed a database review comparing the clinical outcomes of patients undergoing TKA for PVNS versus osteoarthritis from 2007 to 2016. They found that the PVNS patients had a higher rate of post-operative complications, most notably higher rates of stiffness at 1 year (odds ratio 1.48, p = 0.023) and infection at 2 years (odds ratio 1.73, p = 0.011).…”
Section: Pigmented Villonodular Synovitismentioning
confidence: 99%